Phytochemical Profile and Hair Growth Activity of Marigold Flower (Tagetes erecta L.) Extract - Lia Puspitasari; Putu Indrayoni; Putu Ayudia Septiarini (Department of Mathematics and Science Education, Faculty of Teacher Training and Education, University of Mataram. Jurnal Pijar MIPA colaborates with Perkumpulan Pendidik IPA Indonesia Wilayah Nusa Tenggara Barat, 2026)
The Marygold flower (Tagetes erecta L.) exhibits numerous pharmacological properties. The marigold flower promotes hair development. Antioxidant substances that contribute to hair growth include alkaloids, flavonoids, tannins, and saponins. This research was conducted to determine the efficacy of ethanol extracts from Marygold flowers (Tagetes Erecta L.) as hair growers in male rabbits (Oryctolagus cuniculus). In a post-test-only control-group design, this study employed an experimental methodology. Thirty male rabbits served as test subjects in this study, which used one-way ANOVA. The KTL method was used in this study to determine the chemical constituent content of the ethanol extract of Marygold flowers at 5%, 10%, and 20% concentrations. Then, the length and density of the rabbit hair were measured to test the activity of hair growth. On days 7, 14, and 21, hair growth length was measured. On day 21, however, hair weight (density) was measured. Compounds from the flavonoid group (Rf 0.50 & 0.76), tannins (Rf 0.33 & 0.64), saponins (Rf 0.36 & 0.80), and alkaloids (Rf 0.33 & 0.62) were all positively present in the Marygold flower ethanol extract. The 20% concentration of Marygold flower ethanol extract exhibited the highest activity (p<0.05) in tests of hair density and length growth. The ethanol extract from Marygold flowers promotes hair growth in male rabbits, making their hair longer and denser.